Simulation‐Based Seismic Risk Assessment of Gas Distribution Networks. (3rd November 2014) - Esposito, Simona; Iervolino, Iunio; d'Onofrio, Anna; Santo, Antonio; Cavalieri, Francesco; Franchin, Paolo; Iervolino, Iunio; Ellingwood, Bruce R.
Abstract The basic function of a gas distribution system, essentially composed of buried pipelines, reduction stations, and demand nodes, is to deliver gas from sources to end users. The objective of the article is to discuss the evaluation of seismic risk of gas networks in compliance with the performance‐based earthquake engineering framework adapted to spatially distributed systems. In particular, three issues are addressed: (1) spatial seismic hazard characterization in terms of ground shaking and permanent ground deformation; (2) analysis of system's vulnerability via fragility curves; (3) seismic performance evaluation via computer‐aided simulation. As an application, the seismic risk analysis of L'Aquila (central Italy) gas distribution network, a 621‐km mid‐ and low‐pressure pipeline system was considered. The analyses were performed with reference to the mid‐pressure part of the network, through an object‐oriented software, specific for risk assessment of lifelines, developed by the authors. Results in terms of connectivity‐based performance indicators are presented and discussed, along with a performance disaggregation analysis carried out to evaluate the contribution of the components of the system to the risk.